2022
DOI: 10.1001/jama.2021.23605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of P2Y12 Inhibitors on Survival Free of Organ Support Among Non–Critically Ill Hospitalized Patients With COVID-19

Abstract: IMPORTANCEPlatelets represent a potential therapeutic target for improved clinical outcomes in patients with COVID-19.OBJECTIVE To evaluate the benefits and risks of adding a P2Y12 inhibitor to anticoagulant therapy among non-critically ill patients hospitalized for COVID-19. DESIGN, SETTING, AND PARTICIPANTS An open-label, bayesian, adaptive randomized clinical trial including 562 non-critically ill patients hospitalized for COVID-19 was conducted between February 2021 and June 2021 at 60 hospitals in Brazil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 23 publications
2
79
1
2
Order By: Relevance
“…Another area of debate is whether antiplatelet therapies should be used in combination with anticoagulants for the treatment of patients with COVID-19. Results of the ACTIVE-4a trial, which evaluated non-critically ill, hospitalized patients with COVID-19, found that the addition of a P2Y12 inhibitor to a therapeutic dose of heparin did not improve survival [ 20 ]. Other ongoing ACTIV-4 studies aim to provide more insights about the safety and efficacy of antithrombotic strategies for hospitalized patients with COVID-19 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another area of debate is whether antiplatelet therapies should be used in combination with anticoagulants for the treatment of patients with COVID-19. Results of the ACTIVE-4a trial, which evaluated non-critically ill, hospitalized patients with COVID-19, found that the addition of a P2Y12 inhibitor to a therapeutic dose of heparin did not improve survival [ 20 ]. Other ongoing ACTIV-4 studies aim to provide more insights about the safety and efficacy of antithrombotic strategies for hospitalized patients with COVID-19 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients were taking aspirin (83.9%), with less on clopidogrel (8.2%), dual antiplatelet therapy (7.4%), or ticagrelor or prasugrel, and the authors did not break down differences between therapies. The ACTIV-4a multicenter RCT compared heparin anticoagulation alone to added P2Y12 inhibitor administration (ticagrelor or clopidogrel) and found no significant benefit amongst 2219 non-critically ill patients, including no difference in days free of respiratory or cardiovascular support and major thrombotic events [ 98 ]. Similar trials with much smaller populations of less than 100 patients on antiplatelet therapy, most on aspirin, found no significant mortality benefit compared to controls [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of anticoagulation with DOACs may be useful in patients for a month postdischarge, 69 hospitalization for COVID-19, antiplatelet and antithrombotic therapy has thus far shown no benefit. 54,55 When determining whether or not to initiate anticoagulation in COVID-19 positive patients, it is essential to consider their severity of illness as disease progresses, comorbidities, drug interactions, and any pertinent laboratory values that can help weigh the risks and benefits of whether or not to anticoagulate.…”
Section: Discussionmentioning
confidence: 99%